Design and development of SMED quick die change tools for small press dies - Siti Solehah, Mohd Rusadi (2013)
The single minute exchange of die is tools of lean production system and most commonly implement in batch production. This review article presents the design and development of single minute exchange of dies (SMED) quick die change tool for small press cut machine. The purpose is to eliminate the wastage of non value added activities involve during internal changeover time. Changeover time is the time elapsed between the last pieces in the run just completed until the first good piece from the process after the changeover. Also, to design and fabricate the intermediate jigs as to support the acceleration of changeover time. By this, it will reflect on the improvement of the production process by increasing the flexibility to meet the changing customer demands. This flexibility need to be achieved in any production plant for scheduling the production process and activity to be suite with the customer demand without ignoring the MUDA wastages. Designing a flexible improvement just to simplify the operator job during the setup time by follows the best ergonomic posture. All the implementation will give a result to the shorten changeover time in a single digit minutes which is the deduction of 75.9% changeover time. Plus, this project also gives a huge impact on man power usage in internal preparation from 2 man power to 1. The project will be conducted as follows to the steps of SMED directed by Sheigo Shingo.